Evaluasi Prosedur Audit atas Persediaan Obat-Obatan pada Rumah Sakit X Oleh Kantor Akuntan Publik ZYX - Azmiyanti, Rizdina; Putra, Nieto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Inventory of medicines in hospitals is an important and significant asset. The inventory of medicines must be adjusted to meet the substantial treatment needs of the hospital, as inadequate pharmacy efficiency can prevent healthcare services in the hospital. The inventory of medicines in hospitals hold significant importance as it impacts the quality of service delivery. Therefore, auditors perform inventory audit procedures to verify that the inventory reported in the financial statements is consistent and accurate with the actual conditions in the field. The purpose of this research is to evaluate the performance of auditors in auditing financial statements, especially focusing on inventory accounts. The method used is a qualitative descriptive method with primary data sources from interviews with auditors at the Public Accounting Firm (KAP). Advices for auditors at KAP ZYX are improving their skills and knowledge regarding the audit process or the latest regulations through training and experience that can increase their insight.